Capecitabine and Celecoxib as a Promising Therapy for Thymic Neoplasms. (October 2018) - Wood, Kevin; Byron, Elizabeth; Janisch, Linda; Salgia, Ravi; Sharma, Manish R.
Abstract : Objectives: For patients with unresectable or metastatic thymic epithelial neoplasms, few therapy options are available and outcomes are poor. This case series demonstrates that the combination of capecitabine and celecoxib may be a promising therapeutic option for these patients. Materials and Methods: The current report describes the outcomes of 5 patients with thymic neoplasms treated on a drug-drug interaction study of capecitabine and celecoxib in patients with advanced solid malignancies (NCT01705106) conducted at the University of Chicago, plus a sixth patient treated with the same regimen outside of the protocol. Results: Six patients with thymic neoplasms were treated with capecitabine 1000 mg/m 2 twice daily and celecoxib 200 mg twice daily, day 1 to day 14 on a 21-day cycle. This included 3 patients with thymic carcinoma, 1 with thymic neuroendocrine tumor, and 2 with thymomas. Objective response rates were noted in 3 of 6 patients. Two of the 3 thymic carcinoma patients had complete responses, and the third had a partial response. Best response for the other patients included stable disease for both thymoma patients and progressive disease for the thymic neuroendocrine patient. Other than grade 3 palmar-plantar erythrodysesthesia, which developed in 4 of 6 patients and required dose reductions, the regimen was well tolerated. Conclusions: This case series suggests that capecitabine plus celecoxib may be an effective and well-tolerated treatment option for patients with thymic carcinoma. Further studies should be carried out to establish the efficacy of capecitabine plus celecoxib in thymic carcinoma, and to determine whether monotherapy with capecitabine would be similarly effective.